The rjing gene is required for embryonic brain development in Drosophila. - Sedaghat, Y.; Sonnenfeld, M. (Development genes and evolution, 2002)
Loss- and gain-of-function studies have demonstrated a crucial role for the jing zinc finger transcription factor in neuronal and glial differentiation and survival in the embryonic central nervous system midline of Drosophila. Here, we have studied the role of jing during embryonic brain development. Proper jing function is required for the formation of the primary brain axon scaffold. In homozygous jing (3) mutant embryos the preoral commissure is not pioneered and never forms. Other axon pathways are pioneered but subsequently do not form properly, including the postoral tritocerebral commissure, the circumesophageal connectives and the pathways that connect the brain with the ventral nerve cord. To understand the cellular basis of the axon phenotype the jing expression pattern in the brain was characterized using a jing-lacZ enhancer trap. jing-lacZ enhancer trap expression occurs in glia and neurons in the brain midline and lateral clusters as determined by co-localization of the lacZ gene product with Repo and Castor, respectively. In addition, the jing-lacZ enhancer trap and the basic helix-loop-helix-PAS gene, single-minded ( sim), are expressed in the only glial midline cluster present in stage-14 wild-type embryos. jing function is required for the differentiation of Repo-, Castor- and Sim-positive cells in the embryonic brain as each of these populations contain a reduced number of cells in homozygous jing (3) mutant embryos. We further find that jing is required for neuronal and glial survival as repo- and castor-expressing cells undergo cell death in homozygous jing (3) mutant embryos, as revealed by double labeling with Tunel. Expression of jing in sim-expressing cells in the brain disrupts the entire axon scaffold but most significantly results in loss of the preoral and postoral tritocerebral commissures. In addition, circumesophageal connectives are repelled after expression of two copies of UAS- jing in sim-expressing cells, suggesting the activation of axon repellent molecules. Over-expression of sim in the brain is also associated with loss of preoral and postoral tritocerebral commissures. Therefore, the proper dosage of jing and sim in the brain is critical for the formation of the primary axon scaffold. These results show that an important role for jing in the developing brain is the regulation of neuronal and glial differentiation and survival.